Transmission of methicillin-resistant Staphylococcus pseudintermedius between infected dogs and cats and contact pets, humans and the environment in households and veterinary clinics - van Duijkeren, E.; Kamphuis, M.; van der Mije, I.C.; Laarhoven, L.M.; Duim, B.; Wagenaar, J.A.; Houwers, D.J. (Veterinary microbiology, 2011)
The objective of this study was to investigate the prevalence of methicillin-resistant Staphylococcus pseudintermedius (MRSP) in people, pets and the environment in households with a pet with a clinical MRSP-infection within the past year. Personnel and the environment at veterinary clinics were also screened. Nasal swabs (humans), nasal and perineal swabs (pets) and environmental wipes were examined using selective culturing. Twenty households were enrolled; 10/20 index cases still had clinical signs of infection at the start of the study and all were MRSP-positive. Of the remaining 10 index cases five were MRSP-positive in nasal and/or perineal samples. Five of 14 (36%) contact dogs and four of 13 (31%) contact cats were found MRSP-positive. In the households with an index case with clinical signs of infection 6/7 (86%) contact animals were MRSP-positive. MRSP was cultured from 2/45 (4%) human nasal samples. Domestic contamination was widespread as positive samples were found in 70% of the households and 44% of all environmental samples were MRSP-positive. In all but one of these MRSP-positive households the index case was still MRSP positive. Among the personnel in veterinary clinics 4/141 (3%) were MRSP-positive. MRSP was cultured from 31/200 environmental samples in 7/13 clinics at the first sampling and in 3/6 clinics the environment remained MRSP-positive after cleaning and disinfection indicating that current cleaning procedures often were unable to eliminate MRSP. These results show that transmission of MRSP between infected or colonized dogs and cats and healthy people does occur but is relatively uncommon, while transmission to contact pets occurs frequently, especially when the index case still has clinical signs of MRSP-infection.